Hybrid markerless augmented reality tracking method for planar surface - Fadhil Noer Afif, 1990-; Ahmad Hoirul Basori, supervisor; Fakulti Komputeran (2013)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2013